ANALISIS IMPLEMENTASI PROGRAM SEKOLAH RAKYAT DALAM PERENCANAAN PEMBANGUNAN DAERAH PROVINSI BANTEN - Ririn Rindriyani Durrotun Nisa; Laeli Nur Khanifah; Salma Zulayka; Aziza Nawra Pasya; Ananda Khansa Sayidina; Ananda Chanaya Meutya Lestari (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The Sekolah Rakyat Program is a government initiative aimed at improving educational access for poor and extremely poor communities while supporting equitable regional development. This study aims to analyze the implementation of the Sekolah Rakyat Program within the regional development planning framework of Banten Province using George C. Edwards III's policy implementation perspective. The research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, observation, documentation, and literature review, and were analyzed through data reduction, presentation, and interpretation. The findings indicate that the program implementation is supported by relatively effective communication, adequate resources, positive implementer disposition, and a well-coordinated bureaucratic structure. However, several challenges remain, including limited land availability, complex inter-agency coordination, disparities in regional capacity, and resistance from some community members toward the boarding school system. Keywords: educational access; policy implementation; regional development; Sekolah Rakyat